Digital Screen Time and Associated Health Factors: A Bibliometric Study on Global Research Trends Between 2012-2023 - Singh, Arti; Lekha, P. Padma Sri; Jadhav, Bhoomika N.; Azeez, E.P. Abdul (Adolescent Psychiatry, 2025)
BackgroundScreen time has become an inevitable aspect of daily life due to increased technological access and changes in the social and economic landscapes. The increase in screen time is associated with the development of various health conditions. Contextually, research on screen time and its health impact has been studied widely. Therefore, the present study tried to understand the trends and themes in the global research on screen time and its associated health aspects.MethodsWe adopted a bibliometric review, and the data were extracted from the SCOPUS database, limiting it to 2012-2023 (n =4077). The final number of studies considered for the analysis were 2919 after applying the inclusion and exclusion criteria.ResultsScientific production has increased over the years on this topic, with few consistent contributors (Tremblay MS, Chaput JP, and Carson V) and sources from Western countries leading the production in this domain. In addition, from the results of thematic network mapping, we identified the basic yet underdeveloped topics in screen time and health research, namely obesity, risk factors to health, and mental health. A good proportion of the studies involve children and adolescents as participants, indicating the growing trend of studying screen time risk factors for these age groups' health.ConclusionIt was evident from the result that the earlier works have focused on screen time as a risk to health and well-being. However, its role in specific health conditions is underdeveloped. Further, the case of adolescents and children being a widely studied age group suggests the implications for their health and mental health.
Keywords: psychological health